Data from: Maternal immunization increases nestling energy expenditure, immune function, and fledging success in a passerine bird - Burness, Gary; Moher, Deanna; Ben-Ezra, Noah; Kelly, Ryan J; Hasselquist, Dennis; Chin, Eunice H (Dryad, 2018)
Female birds transfer maternally-derived antibodies (matAb) to their
nestlings, via the egg yolk. These antibodies are thought to provide
passive protection, and allow nestlings to avoid the costs associated with
mounting an innate immune response. To test whether there is an energetic
benefit to nestlings of receiving matAb, we challenged adult female tree
swallows (Tachycineta bicolor) prior to clutch initiation with either
lipopolysaccharide (LPS) or saline (Control). Following hatching, one half
of each females nestlings were immunized on day 8 post-hatch with LPS or
saline, and for 4-hrs post immunization nestling metabolic rate (MR) was
measured. There was no difference in either LPS-reactive antibodies or
total Ig levels between offspring of immunized and non-immunized mothers
on day 6 or 14 post-hatch, possibly reflecting a relatively short
half-life of matAbs in altricial birds. Additionally, we found no evidence
that nestlings from LPS-immunized mothers could avoid the
growth-suppression that may result from activation of an inflammatory
response. Unexpectedly, we found that control-nestlings from LPS-mothers
had higher resting MR than control-nestlings of control-mothers. We
attribute the increased MR to the costs associated with a general
nonspecific enhancement of immune function in nestlings from LPS-immunized
mothers. Consistent with enhanced immune function, nestlings of immunized
mothers had a more robust inflammatory response to phytohaemagglutinin,
and higher fledging success. Our results suggest maternal antigen exposure
pre-laying can result in increased fitness for both mothers and offspring,
depending on food availability.
Tree swallow maternal immunization dataTree swallow maternal immunization
hatching success dataTree swallow maternal immunization fledging success
data
Keywords: mismatch hypothesis; maternal effects; Tachycineta bicolor; energetics; maternal antibody transmission